The profit centers based management - Verboncu Ion (Budgetary Research Review (BRR), 2010)
One of the most complex and sophisticated managerial tools is the profit centers based management. Promoting and using the profit centers based management in the Romanian companies represents a condition for the economic and commercial success. By its content, the profit centers based management ensures order, discipline, and stringency in running the work processes, efficiency and effectiveness generating characteristic.
Keywords: M11; 330; management by objectives; management by budgets; profit centers; budgets; managerial and economic decentralization